The effect of graphene addition on the microstructure and properties of graphene/copper composites for sustainable energy materials - Jamadon, Nashrah Hani; Muhamad Rasid, Nurul Izzati; Ahmad, Mohd Azwan; Lutfi, Maisarah; Syed Abu Bakar, Syarifah Adzila; Jamal, Nur Ayuni; Muhamad, Norhamidi (IOP Publishing, 2023)
Graphene is a single thin layer (mono layer) of a hexagon-bound carbon atom and is an allotropic carbon in the form of a hybrid atomic plane, with a molecular bond length of 0.142 nm. Graphene is the thinnest and lightest material with 0.77 mg square meters, which exhibited excellent electricity and heat conductor. However, the perfect uniform microstructure, strength and optimum thermal properties of copper-graphene composites cannot be achieved because the amount of graphene does not reach the optimum level. In order to solve this problem, copper-graphene composites were produced by metal injection molding method (MIM) with various percentage of graphene, specifically 0.5%, 1.0% and 1.5% in the composite, to compare the physical and mechanical properties of these samples. MIM process involves the preparation of feed materials, pre-mixing process, mixing process, mold injection process, binding process and sintering processes. Feeding materials were used are copper and graphene, which have the powder loading of 62% with a mix of binder comprising 73% polyethylene glycol (PEG), 25% polymethyl methacrylate (PMMA), and 2% stearic acid (SA). Densification and tensile test were conducted to determine the mechanical properties. Scanning electron microstructure (SEM) was performed to obtain the microstructure of the composites. From the research, the result revealed that the 0.5% graphene content had the optimum parameter, which the hardness and tensile stress values were at 94.2 HRL and 205.22 MPa.